Safety and efficacy of submucosal tunneling endoscopic septum division for epiphrenic diverticula - Li, Xuan; Zhang, Weifeng; Yang, Juliana; Wang, Xiaoyong; Dang, Yini; Hu, Bin; Cai, Qiang; Zhou, Pinghong; Zhang, Guoxin (Endoscopy, 2019)
Background Symptomatic epiphrenic diverticula are mostly treated with laparoscopic diverticulectomy. Our study aimed to demonstrate the safety and efficacy of submucosal tunneling endoscopic septum division (STESD) for treatment of symptomatic epiphrenic diverticula.Methods Data from patients with epiphrenic diverticula who had undergone STESD were retrospectively reviewed. The parameters analyzed were the modified Eckardt score, total procedure time, length of hospital stay (LOS), number of clips used, adverse events, and patient satisfaction.Results A total of eight patients (5 men; mean [standard deviation (SD)] age 66.25 [7.17] years) were enrolled in our study. The mean (SD) size of epiphrenic diverticula was 3.68 (1.59) cm. The mean (SD) procedure time was 52.87 (22.47) minutes, with a median number of six clips being applied. The modified Eckardt score significantly decreased post-procedure (P < 0.001). The mean (SD) LOS was 5.87 (0.83) days. No adverse events or symptom recurrences were reported.Conclusion STESD is a safe and effective technique to be performed in the submucosal tunnel for the management of patients with epiphrenic diverticula.